2013
DOI: 10.1016/j.bjid.2013.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Association between vitamin B12 level and anti-parietal cells and anti-intrinsic factor antibodies among adult Jordanian patients with Helicobacter pylori infection

Abstract: Patients with H. pylori infection are more likely to have anti-parietal cell antibodies and anti-intrinsic factor antibodies. There was an association between H. pylori infection and lower vitamin B12 levels. H. pylori infection might be a significant factor in the pathogenesis of autoimmune gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 13 publications
1
10
0
4
Order By: Relevance
“…Firstly, over half (54.5%) of patients with AIG also had evidence of bacterial infection by biopsy and/or UBT, suggesting the possibility that IM may have also been related to H. pylori rather than being exclusively attributed to hypochlorhydria from autoimmune loss of parietal cells. Moreover, it may support emerging evidence of a causative link between H. pylori and autoimmune gastritis, as evidenced by reports of a significant association between H. pylori infection and presence of APCA and antibodies to an intrinsic factor (AIFA) (22). In our study, 44% of AIG patients with negative histology had evidence of infection on UBT.…”
Section: Discussionsupporting
confidence: 88%
“…Firstly, over half (54.5%) of patients with AIG also had evidence of bacterial infection by biopsy and/or UBT, suggesting the possibility that IM may have also been related to H. pylori rather than being exclusively attributed to hypochlorhydria from autoimmune loss of parietal cells. Moreover, it may support emerging evidence of a causative link between H. pylori and autoimmune gastritis, as evidenced by reports of a significant association between H. pylori infection and presence of APCA and antibodies to an intrinsic factor (AIFA) (22). In our study, 44% of AIG patients with negative histology had evidence of infection on UBT.…”
Section: Discussionsupporting
confidence: 88%
“…These results are in agreement with previous studies from other Arabic countries including Jordan and Saudi Arabia. 16 , 17 There was no significant correlation between H. pylori infection and age. These results are in agreement with Khan who concluded that H. pylori infection is acquired early in life and there is no rise in the incidence with advancing age.…”
Section: Discussionmentioning
confidence: 85%
“…Furthermore, Ayesh et al found that people with H . pylori infection had lower levels of vitamin B12 [ 36 ]. In addition, low plasma levels of vitamin B12 may be associated with low bone mineral density [ 37 ].…”
Section: Discussionmentioning
confidence: 99%